Jak rozporządzenie Bruksela I bis rozstrzyga o jurysdykcji w sporach z międzynarodowej gwarancji ubezpieczeniowej, czyli o pojęciu sprawy ubezpieczeniowej - Fuchs, Dariusz (Problemy Prawa Prywatnego Międzynarodowego, 2020)
The article presents the issue of the jurisdiction of a civil court in the light of the provisions of the EU Brussels I bis Regulation in relation to a matter in the field of insurance guarantee. This was presented against the background of qualification considerations of the insurance case and delimitation of the norms of the EU Brussels I bis Regulation in relation to disputes under the insurance contract from reinsurance disputes (in the strict sense and the so-called retrocession). At the same time, reasons were given for excluding social security from this scope. Because in practice (and in theoretical approaches) there are discrepancies as to the scope of the subject application of the standards in relation to individual insurance activities, one of the objectives of this study is to indicate that such nterpretation possibility which such a gap will remove, because it is even be harmful to the certainty of turnover, if it would appear in relation to such fundamental concepts as jurisdiction in international insurance disputes and jurisdiction in domestic disputes. Consequently, basically based on an autonomous interpretation and in the alternative: lex fori the possibility of refusing to apply the standards of section 3 of EU Regulation No. 1215/2012 to disputes in the field of insurance guarantee. An appropriate analysis of national law was also carried out, indicating the need for coherence between EU and internal law standards in the area of qualifying disputes arising from the insurance guarantee.